Ekonomi Politik Media dalam Pemberitaan BRICS pada The Jakarta Post Model Vincent Mosco - Moch Krisna Pambudi Utomo; Masnia Ningsih; Moch Icdah Asyarin Hayau Lailin (Pusat Riset dan Inovasi Nasional, 2025)
The global economic crisis has prompted developing countries, including the BRICS group (Brazil, Russia, India, China, and South Africa), to strengthen cooperation in creating a multipolar economic order as a form of resistance to Western domination. Mass media plays a crucial role in framing this dynamic. This study aims to examine how The Jakarta Post constructs the BRICS narrative through three main dimensions in Vincent Mosco's Political Economy of Communication theory: commodification, spatialization, and structuring. This study uses a descriptive qualitative approach, with data collection techniques in the form of documentation and analysis of news published in The Jakarta Post between June 18, 2024, and January 31, 2025. Data were categorized based on the type of information and main themes, then analyzed using Mosco's theoretical concepts. The results show that the commodification process occurs when geopolitical issues, such as Indonesia's opportunity to join BRICS, are transformed into media commodities appealing to elite readers and strategic economic actors. This practice also involves the contribution of experts, but often without equitable compensation. Spatialization is reflected in the real-time distribution of digital content that transcends geographical and temporal boundaries, strengthening the penetration of BRICS discourse into the international public sphere. Structuralization emerges in the narrative of building a new world order through BRICS agendas such as dedollarization, technological integration, and alternative payment systems, although it remains overshadowed by the dominance of Western financial institutions. Thus, media coverage not only represents geopolitical dynamics but also transforms strategic issues into information products with economic value, while revealing the tension between the aspirations of developing countries and established global hegemony.